Kualitas Pelayanan Penyaluran Tunjangan Profesi Guru di Kabupaten Fakfak - Marini, Heti; Wulandari, Septi; Septian, Esa; Ximenes, Manuel (Universitas Bojonegoro, 2026)
This study aims to analyze the quality of Teacher Professional Allowance (TPG) distribution services at the Fakfak Regency Education, Youth, and Sports Office. This study uses a descriptive method with a quantitative approach through a survey of certified teachers. Data used were obtained using a Likert scale to measure teachers' perceptions of the quality of service provided, including aspects of reliability, assurance, direct evidence, empathy, and responsiveness. The results show that most service quality attributes have met user expectations, but there are several attributes that still need improvement, especially in terms of the speed and accuracy of teacher data monitoring through the Dapodik application. Based on the results of the Importance Performance Analysis (IPA), attributes that need to be prioritized for improvement are services related to data accuracy and procedures that facilitate users. This study provides recommendations for improving the quality of service in TPG distribution to make it more efficient and in line with teacher expectations. .